Leadership of School Administrators Based on Sangahavatthu IV Affecting of Teacher’s Performances at Under the Office Nonthaburi Primary Education Service Area 1 - Songmueng, Phongsatorn; saccaguna, Phra Suvaddhana (Journal of Dhamma for Life, 2025)
The objectives of this thesis were as follows: 1) to study Leadership of school administrators based on SANGAHAVATTHU IV under Nonthaburi Primary Educational Service Area Office 1 2) To study the motivation of teacher’s performances under Nonthaburi Primary Educational Service Area Office 1 3) To study the study Leadership of school administrators based on SANGAHAVATTHU IV Affecting motivation of teacher’s performances under Nonthaburi Primary Educational Service Area Office 1 Population in this research was School administrators and teachers under the Nonthaburi Primary Educational Service Area Office 1, using a sample of 297 people. Analyze data using ready-made programs Statistics used in data analysis include frequency, percentage, average (Arithmetic Mean: "") Standard Deviation (S.D.) Hypothesis Test Stepwise Multiple Regression Analysis The results of research were found that: 1) Leadership of school administrators based on SANGAHAVATTHU IV under Nonthaburi Primary Educational Service Area Office 1 as a whole is at a highest level. When considering each aspect, it was found that all aspects were at the highest level. The average values, ranked from highest to lowest, were as follows: leadership of school administrators in charity; leadership of school administrators in self-discipline; leadership of school administrators in unity; and leadership of school administrators in kind speech, respectively. 2)The motivation of teacher’s performances under Nonthaburi Primary Educational Service Area Office 1 as a whole is at a highest level. When considering each aspect, it was found that all aspects were at the highest level. The average values, ranked from highest to lowest, were as follows: responsibility, nature of work performed, advancement, success of work, and respect, respectively. 3) Leadership of school administrators based on SANGAHAVATTHU IV Affecting motivation of teacher’s performances under Nonthaburi Primary Educational Service Area Office 1 the leadership of school administrators in terms of unity, the leadership of school administrators in terms of kindness of speech, and the leadership of school administrators in terms of charity, with a multiple correlation coefficient of 50.8 % (R2 = 0.508), with statistical significance at the .01 level, can be predicted in terms of raw scores and standard scores as follows: Forecast equations in raw score form 𝑌 ′ = 1.744+ .304 + .216 + .110 Forecast equations in standard score form 𝑍’ = 367 + .279 +.129